2015
DOI: 10.1016/j.nimb.2015.02.074
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, thermal stability and the effects of ion irradiation in amorphous Si–O–C alloys

Abstract: a b s t r a c tAmorphous films of Si-O-C alloys were synthesized via sputtering deposition at room temperature. These alloys were characterized using grazing incidence diffraction, both as a function of temperature and irradiation dose. It was found that the material retained its amorphous structure, both at high temperatures (up to 1200°C) and ion irradiation doses up to 1.0 dpa. The depth profile from photoemission spectroscopy provided evidence of the oxidation state of these alloys and their atomic composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…Previous studies have shown that SiOC alloys remain amorphous after both room temperature (RT) and 600°C irradiation with damage levels up to 20 displacement per atom (dpa). [11,12] To step toward applications, an amorphous SiOC/crystalline Fe composite has been developed. α-Fe was as a model material for steel.…”
Section: (Received 3 August 2015; Final Form 30 September 2015)mentioning
confidence: 99%
“…Previous studies have shown that SiOC alloys remain amorphous after both room temperature (RT) and 600°C irradiation with damage levels up to 20 displacement per atom (dpa). [11,12] To step toward applications, an amorphous SiOC/crystalline Fe composite has been developed. α-Fe was as a model material for steel.…”
Section: (Received 3 August 2015; Final Form 30 September 2015)mentioning
confidence: 99%
“…Therefore, these materials feature both SiO 2 and SiC bonds. This leads to the strengthening of glass structure and enhancement of its properties, i.e., chemical, thermal, and oxidation resistance [1][2][3][4]. Two main concepts of silicon oxycarbide structures exist.…”
Section: Introductionmentioning
confidence: 99%
“…Changing the precursor can lead to formation of different black glasses, e.g., materials with or without free carbon phase [5,7,15,35]. From the variety of possible applications, at least few should be mentioned, i.e., anodes for Li-ion batteries [16], material for artificial heart valves [17], and protective coatings [4]. Most of the research focuses on two temperature ranges used to obtain SiOC glasses-below 400°C for low-k thin layers and above 1000°C, where phase separations occurs [4,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the interesting applications is their utilization as structural materials in harsh ambient and high temperatures. This situation only is possible due to their adequate and satisfactory properties such as mechanical [3], thermal [4], oxidation resistance [5] and compositional stability [6].…”
Section: Introductionmentioning
confidence: 99%